2012
DOI: 10.1111/j.1582-4934.2011.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

NK cells engineered to express a GD2‐specific antigen receptor display built‐in ADCC‐like activity against tumour cells of neuroectodermal origin

Abstract: Treatment of high-risk neuroblastoma (NB) represents a major challenge in paediatric oncology. Alternative therapeutic strategies include antibodies targeting the disialoganglioside GD2, which is expressed at high levels on NB cells, and infusion of donor-derived natural killer (NK) cells. To combine specific antibody-mediated recognition of NB cells with the potent cytotoxic activity of NK cells, here we generated clonal derivatives of the clinically applicable human NK cell line NK-92 that stably express a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(113 citation statements)
references
References 45 publications
2
105
1
1
Order By: Relevance
“…However, concern has been raised about genetically modified autoreactive T cells, which might cause undesirable side effects after infusion into patients. NK cells, in contrast, do not possess TCR-like molecules that might (21,(41)(42)(43)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, concern has been raised about genetically modified autoreactive T cells, which might cause undesirable side effects after infusion into patients. NK cells, in contrast, do not possess TCR-like molecules that might (21,(41)(42)(43)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%
“…3 were also incubated with the bladder carcinoma cell lines RT4 and HT1376, which show endogenous expression of PSCA. *p , 0.05. edge, we treated for the first time established solid tumors with CAR-modified NK cells, whereas other groups favored mixing of NK cells and target cells prior to tumor transplantation (23,(65)(66)(67) or chose an experimental setting that most likely confronts injected tumor cells and CAR-modified NK cells in the bloodstream or lung capillaries (67). In this article, we demonstrate that treatment with YTS anti-PSCA-DAP12 NK cells resulted in a significantly delayed growth of PSCA-positive tumors when compared with tumors treated with YTS wt cells and YTS myc-DAP12 controls, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…142) and CD20 (REF. 143) expressed on B cell malignancies; disialoganglioside G D2 , a glycolipid expressed on neuroblastoma 144 and various other cancer types 145 ; HER2 (also known as ERBB2), an antigen expressed by tumours of epithelial origin [146][147][148] ; epithelial cell adhesion molecule (EPCAM), a molecule over expressed by carcinomas and cancer stem cells 149 ; HLA-A2 loaded with the mela noma antigen gp100 (also known as PMEL) 150 ; prostate stem cell antigen (PSCA) 151 ; and CD138 (also known as SYND1), which is expressed by multiple myeloma cells 152 . Because NK-92 cells are a tumour cell line infected with Epstein-Barr virus (EBV), they must be irradiated to prevent their proliferation before being adoptively transferred.…”
Section: Using Nk Cells For Cancer Therapymentioning
confidence: 99%
“…Investigations have shown that NK cells transduced with anti-CD19 CAR or NKG2D are potent against B-lineage and osteosarcoma cells in vivo and in vitro (49,52). CAR þ cells have been generated against GD2 in neuroblastoma and CD33/CD123 in myeloid leukemia (51,53,54 …”
Section: Nk Cell Bioprocessing Ex Vivomentioning
confidence: 99%